Employers’ and Entry-Level Job Seekers’ Expectations: Are They Similar? - Quah, Chun Hoo; Lim, Hwee Ling (INTI Publishing House Sdn Bhd, 2006)
The problem of unemployed graduates’ ¡s not of recent origin. Every year thousands of fresh graduates leave their educational institutions for the world of work. The main purpose of this study was to examine whether the perceived values, skills and abilities of 180 final year accounting and management students are similar to those of employers. In addition, this study also sought to determine whether entry-level job seekers’ perceptions were influenced by gender, ethnicity and major field of study. Using a questionnaire survey, this study found that employers and entry-level job seekers differed in their perceptions as per the most desired values and abilities sought in an entry-level job seeker. Whilst gender had no effect on the perceived abilities and skills of entry-level job seekers, there appeared to be some difference in the perceived values amongst gender